Pengaruh Model Pembelajaran Kooperatif Teams Games Tournament Terhadap Minat Belajar IPAS Siswa Kelas IV SDIT Al Akhyar - Fella Putri; Megawati Megawati; Abdulah Abdulah (CV. Master Literasi Indonesia, 2026)
This study aims to “determine the effects of the Teams Games Tournament (TGT) cooperative learning model on the learning interests of fourth-grade IPAS students at SDIT Al Akhyar. This study used an experimental approach using a one-group pretest-posttest design”. The research sample consisted of eighteen fourth-graders from class A. Questionnaires were used to gather information on students' interest in learning both before (pretest) and after (posttest) the intervention. With pretest scores averaging 75% and posttest scores averaging 82%, the findings demonstrated a considerable rise in students' motivation in studying. “The null hypothesis was rejected and the alternative hypothesis was accepted when the hypothesis test yielded a significance value (Sig.2-tailed) of 0.001 (p < 0.05)”. According to this, the TGT cooperative learning model successfully raises students' interest in IPAS, indicating that it has the potential to be used as an alternate teaching strategy, especially for Indonesian economic activity materials.